CMET-20. ANALYSIS OF NANO-SIZED PARTICLE IN HUMAN CEREBROSPINAL FLUID: A MEASUREMENT OF EXTRACELLULAR VESICLE CONCENTRATION CHANGE WITH MIR-21 EXPRESSION AFTER CHEMOTHERAPY FOR LEPTOMENINGEAL CARCINOMATOSIS. (11th November 2019) - Lee, Kyue-Yim; Lin, Wei-wei; Gwak, Ho-Shin; Heon Kim, Jong; Chul Yoo, Byong; Kim, Tae-Hoon; Bae Park, Jong; Jin Park, Hyeon; Kim, Ho-Jin; Woong Kwon, Ji; Hoon Shin, Sang; Yoo, Heon
Abstract: PURPOSE: For comparing the distribution and concentrations of nano-sized micro-molecules in cerebrospinal fluid (CSF) according to different central nervous system (CNS) disease METHODS: We have collected CSF of 447 patients from 6 different groups (systemic cancer, healthy control, leptomeningeal carcinomatosis (LMC), brain metastasis, other brain tumor, and other CNS disease). After cell down by centrifugation, proportion of nano-sized particle is measured by Nano-sizer and absolute number of extracellular vesicle (EV, 100–1, 000 nm) is counted by Nano-sight. We verified exosomes in our CSF samples by exosome purification and Western blot. RESULTS: In Nano-sizer, two peaks appeared at mean 10.5 nm and 174 nm. The small peak is presumed to be nucleic acid and protein as we could decrease or eliminate the peak by nucleic acid elimination kit or proteinase. The proportion of large peak, presumed to represent EVs, is significantly higher in LMC group than all other groups (mean 64% vs. 44%, p < 0.001). And also, the count of EV is significantly higher in patients with LMC (7.15 x 10 8 vs. 3.46 x 10 8, p < 0.001). Furthermore, we evaluated paired EV concentration of pre- and post-treatment of intra-CSF chemotherapy in non-small lung cancer patients with LMC ( n =33). Overall survival of patients was significantly prolonged in patients with increased EV count compared to those of decreased or 'no-change' (< 20%) (442 vs. 165 days, p < 0.001). The expression level of onco-microRNA (miR-21) is decreased significantly after the treatment in this favorable prognostic group ( p < 0.01). CONCLUSION: We expect to obtain appropriate variables representing cancer cell activity in the CSF samples by observing this nano-sized molecule proportion and EV concentration with onco-miR expression. KEY WORDS: cerebrospinal fluid, exosome, extracellular vesicle, microRNA, leptomeningeal carcinomatosis